Chemical-guided SHAPE sequencing (cgSHAPE-seq) informs the binding site of RNA-degrading chimeras targeting SARS-CoV-2 5’ untranslated region - Zhichao Tang; Shalakha Hegde; Siyuan Hao; Manikandan Selvaraju; Jianming Qiu; Jingxin Wang (Nature Communications)
Abstract One of the hallmarks of RNA viruses is highly structured untranslated regions (UTRs) which are often essential for viral replication, transcription, or translation. In this report, we discovered a series of coumarin derivatives that bind to a four-way RNA helix called SL5 in the 5’ UTR of the SARS-CoV-2 RNA genome. To locate the binding site, we developed a sequencing-based method namely cgSHAPE-seq, in which an acylating probe was directed to crosslink with the 2’-OH group of ribose at the binding site to create read-through mutations during reverse transcription. cgSHAPE-seq unambiguously determined a bulged G in SL5 as the primary binding site, which was validated through mutagenesis and in vitro binding experiments. The coumarin derivatives were further used as a warhead in designing RNA-degrading chimeras to reduce viral RNA expression levels. The optimized RNA-degrading chimera C64 inhibited live virus replication in lung epithelial carcinoma cells.